Land value and returns on Farmlands: an analysis by Spanish Autonomous Regions - Segura-García del Río, B.; Pérez-Salas, J. L.; Cervelló-Royo, R. (Spanish Journal of Agricultural Research, 2012)
Although the discounted cash-flow is still considered to be the fundamental value of an asset, there are few studies which assess its ability to explain movements in the market prices of agricultural assets. The aim of this work was to compare the evolution of market prices of Farmland to the series of values that would be obtained by applying the income approach method using official Spanish statistical data as well as two proposed methods: on the similarity of the dynamical structure of prices and returns time series, on the one hand; and on the regression between both series, on the other. The results obtained are not consistent with the hypothesis that the values obtained by the income approach method can explain the movements observed in market prices. Only in certain isolated cases, such as the Autonomous Region of Aragón. Therefore, other causes should be considered both at national and regional level.